New Estimates of Intergenerational Mobility in Australia1. Issue 298 (8th June 2016) - Mendolia, Silvia; Siminski, Peter
Abstract : We present new estimates of intergenerational earnings elasticity for Australia. We closely follow the methodology used by Leigh [ BE Journal of Economic Analysis & Policy, 7 (2007) 1], but use considerably more data (12 waves of HILDA and four waves of PSID). Our adjusted estimates are intended to be comparable to those for other countries in Corak [ Journal of Economic Perspectives, 27 (2013) 79]. Our preferred estimate (0.35) is considerably higher than implied by Leigh's study, and is less subject to sampling variation. In an international context, intergenerational mobility in Australia is not particularly high, and is consistent with its relatively high level of cross‐sectional inequality.